A evolução da identidade visual autárquica : da heráldica do século XIII à marca municipal do século XXI - Marques, Tiago Alexandre Campos da Silva, 1980- (2017)
This dissertation proposes an historic perspective on the symbolic identity elements evolution used by municipalities in Portugal, from the 13th century heraldry to the new 21st century municipal brands. Methodologically based on bibliographic revision and documental research, this work describes an historic approach, on the variations of municipal visual identities registered over five timeframes: from 13th to 16th centuries (mainly used in seals); from 16th century to the end of absolute monarchy (with no crown interference); through constitutional monarchy until early 20th century (with crown interference); from 1930 to 1991 (following new legislation and the major municipal heraldry reform); from 1991 to 2016 (following the latest heraldry legislation and analyzing the folding between 20th and 21st centuries). This research reveals that more than half of the municipalities now prefer to use a brand, inthe actual meaning of the term, over their coats of arms, fact which demands a deep reflection about the role of design and designers in this transition. It’s the first approach to this subject at a national scale and through all history. Being a foundational work, the original contribute is focused on the investigational questions raised by it: what’s the political, social, economic and cultural impact revealed by the option of using a brand? What’s the role of design in contemporary heraldry? How to conciliate in project history and contemporariness, facing the new communication challenges municipalities are subject to? What are the consequences of the two coexistent parallel systems (blazon and brand) used to represent municipalities?